Annual Plan 1971-72 Part II-Statements Union Territory of Pondicherry - Planning Commission (Planning Commission, 1971)
Outlay and expenditure Outlay and expenditure - Programmes Plan outlays - Scheme-wise Implement projects costing Rs.1 crore and above Check list in respect of principal projects costing Rs.1 crore and above Physical programmes Outlay and expenditure - Centrally-sponsored schemes.
Union Territory of Pondicherry, Revenue, Finance and Planning Department